KAJIAN PENDISTRIBUSIAN ZAKAT OLEH BAZNAS KOTA PADANG KEPADA MAJLIS TAKLIM BINAAN DITINJAU DARI HUKUM ISLAM - Joni Zulhendra (Fakultas Hukum Universitas Tamansiswa Padang, 2017)
Zakat is one of the economic activities that can alleviate poverty and also help the poor in various parts of the world, especially Indonesia which is experiencing a multidimensional crisis. Therefore, zakat role in restoring the economy and society need professional management. Management of zakat is not merely be individualized from muzakki to mustahik, but carried out by a special institution that handles charity in which people meet certain requirements called amil zakat board. The impetus in this discussion is more specific to the application of Islamic law on the study of the distribution of charity funds by amil zakat board, namely Baznas Padang. Therefore charity is part of the obligation of every Muslim who has the ability, so this research can increase knowledge in the life as a Muslim, in accordance with Islamic teachings. This study, using field with a descriptive qualitative approach that describes the circumstances as they appear in the field next critically analyzed and described in the narrative. The results of this study explained that the distribution of zakat made by Baznas city of Padang to auxiliaries majlis taklim been right on target, because the members who are members of the group were mustahik zakat tergolongan groups and destitute, come from the middle to the bottom who are having difficulty to make ends the necessities of life, children's school fees and treatment if a family member is sick. Implementation of the distribution of zakat carried out by the majlis taklim target Baznas city of Padang to its members is not appropriate, because zakat is the right of mustahik zakat used to help make ends meet, but the board of the group makes loans and indirectly mustahik zakat has been indebted to the rights that should belong to the mustahik.